A Cognitive Linguistics Diagnosing Of Iraqi EFL Students’ Difficulties in Using Synonyms - Nasser, Sura Muttlak (International Journal of Language and Literary Studies, 2021)
Learning and teaching synonyms for Iraqi EFL students is a difficult task. Learning synonyms means learning how words can be related to each other. Understanding synonyms helps students to understand the meaning of the word easily and avoid mistakes committed in synonyms as a result of their knowledge concerning this area. Iraqi EFL students face difficulties in using appropriate synonyms. This study was conducted in the Department of English, College of Education for Women, University of Baghdad, to indicate first-year students’ incompetence in using synonyms. The participants of this study, fifty female students during the first semester, were chosen randomly for the academic year 2019-2020. In order to achieve the aim of this study, the researcher used pre and posttest as tools for collecting data. The data was analyzed by the SPSS program. Figures and tables were used to present the data. The present study reveals the difficulties that occurred when Iraqi EFL students used synonyms. This is due to the need for information about English equivalent words, then suggests suitable solutions for them. Also this study reveals that the domains theory has indeed been demonstrated to be effective in precisely understanding the semantic domains of English lexical concepts.